Improving Students’ Speaking Ability Using Vlog Media at SMK Negeri 1 Arjasa - Ersan, Mohammad; Kurnia, Fabiola D.; Fadilah, Eka (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The primary objective of this study was to ascertain the effectiveness of Vlog and students’ perceptions of its implementation in improving students’ speaking abilities in the 11th grade of APHPi at SMKN 1 Arjasa. This study used a classroom action research design with subjects in the eleventh grade of APHPi (Agribusiness Processing of Fishery Products). The instruments used were pre- and post-tests, as well as a questionnaire. The results indicated that students implemented Vlog in speaking class twice a cycle, and that the results indicated that students were more engaged in speaking class and that the majority of students improved their ability to speak well. The study's findings indicated that students’ achievement increased from the start to the end of the second cycle. The initial condition's average was 65.76, and it increased to 80.30 during the final cycle of the investigation.